Influence of substrate roughness on the wear behaviour of kinetic spray coating. (2020) - Padmini, B.V.; Niranjan, H.B.; Kumar, Ranjeet; Padmavathi, G.; Nagabhushana, N.; Mohan, N.
Abstract: The purpose of the present study was to explore the importance of different substrate roughness on porosity, hardness and wear properties of NiCr based alloy coatings deposited by kinetic spray technique. Low carbon steel was used as the substrate. Different surface roughness levels were attained using different methods like milling, grit blasting and water jet cutting. Coatings were deposited on these substrates utilizing identical coating parameters and technique. The resultant coatings were then investigated for wear behaviour by using a pin on disc wear testing machine for three loads 10, 20 and 30 N and two speeds 0.5 and 1.5 m/s, keeping the sliding distance a constant. Wear rate of substrates and coatings, porosity measurements and hardness of the coatings were investigated. An indication of the results suggests that substrate surface roughness has an influence on the samples studied. The wear resistance of the coating obtained by grit blasting the surface prior to the coating deposition showed the best result.